Manifestações de professores sobre a organização do trabalho educativo para atender os estudantes que terminam o ensino fundamental na vigência dos ciclos e da progressão continuada - Chacoroski, Isabel Cristina (2007)
The central problematic of this research refers to the way in which 8th grade teachers in São Paulo state net with more than 10 years of classroom experience manifested themselves about the organization, in their daily activity, to attend what is foreseen to implement the cycle regime and the continued progression. My study searched and analyzed whatever there was any alteration in the educative process for pupils who have completed the fundamental scholarity in legality of the cycle regime, that is, those who got to the 8th grade or the end of cycle II. The semi-structured interviews where made with two state public school teachers in the peripherical zone of Osasco city, and with three state public school teachers in one school of the north zone of São Paulo city. The answers where grouped around some axis indicating the representative central points of possible alterations in the educative process: continued progression or automatic promotion; classroom work routine; school failure and success; evaluation; evaluation instruments; work routine in evaluation day; registers on pupils performances; analyses of pupil performances in collegiate meetings; planning of reinforcement and recuperation activities; following of reinforcement and recuperation pupils; recuperation pupils performances. The study had as its theoretical reference authors like Gimeno Sacristán, Perez Gómez, Antonio Viñao Frago e Pierre Bourdieu. With the obtained results it was possible to identify the inequalities of positions between the subjects who proposed the reforms and those who ought to execute them, distortions on the theme and concerning the cycles, we can affirm that there was not substantive changes in the way they refer to the teaching action. The teachers testimonials make evident that the seriation has not ended, there is fragmentation of teaching developed time, based on the academic year and on short classes, one fractioned and scaled organization, where teaching is understood under the logics of transmition and learning is subject to the existence of pre-requirements which the pupils do not bring on or bring only a few. About the continued progression, we identified that the term is recurrent, although in the description they make about their pedagogic action, the evaluation of the process is objectively connected to the automatic promotion. There were not verified outstanding impacts which take teachers to look for changes favorable to the students, but to alter points around the maintenance of Brazilian school culture selectivity s structural axis